Comportamiento de 24 líneas promisorias en secano en comparación a CICA 4. - Vargas Daza, Jaime; Aramendiz Oñate, Hernán; Silva Sarmiento, Henry (Instituto Colombiano Agropecuario, 2018)
Arroz-Oryza sativa